Effect of poly(dimethylsiloxane) binder in a silica-based superhydrophobic coating on mechanical properties, surface roughness, and wettability. (September 2020) - Sebastian, Divine; Yao, Chun-Wei
Abstract : Abstract: This work investigates the influence of poly(dimethylsiloxane) (PDMS) within a nanocomposite coating solution constituted by silica nanoparticles and toluene on mechanical properties, surface wettability, and surface morphology. The developed coating's hardness and elastic modulus were studied in detail. A variation in mechanical properties was observed as the amount of PDMS was varied. Also, the average surface roughness, skewness, and kurtosis values show the influence of the amount of PDMS on the surface roughness characteristics of the coating. Furthermore, it was observed that the water contact angles were linked with the proportion of PDMS.